"When we say 'urgent' it means now …". Issue 3 (15th June 2015) - Griffith, Laura; Glasby, Jon
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to describe the perceptions which senior health and social care leaders have of their own organisations and of partner agencies, illustrating a possible method for beginning to think and talk about organisational and professional culture in settings. Design/methodology/approach – This is a practical case study, with a group of senior leaders from across the health and social care system. Findings – Different groups were often more critical of their own organisations than of others, but could still identify certain characteristics that they associated with partner agencies. While there is much that we admire about ourself and others, we seldom get chance to share this positive feedback. Equally, we rarely have the scope to give each other more challenging feedback and this – when carefully facilitated – can help build stronger relationships in the longer term. Research limitations/implications – Inter-agency working is often influenced by the implicit assumptions and stereotypes we hold about each other's professional culture. Surfacing these in a safe, facilitated setting can help to explore and challenge such assumptions (where appropriate), reflect on how we see others and better understand how others see us. Originality/value – Policy debates about integrated care too often focus on structural "solutions" and arguably pay insufficient attention to the importance of culture. While work with front-line practitioners often tries to explore different perceptions of each other, it is less common for such an approach to be attempted with senior leaders.